دور مكاتب الاستشارات الأسرية في تحقيق الاستقرار الأسري لدى المرأة: دراسة تنبؤيه على عينة من سيدات المجتمع المصري - علي، أماني زاهر شحاتة محمد (جامعة الفيوم - كلية الآداب, 2021)
يهدف هذا البحث إلى التعرف على دور مكاتب الاستشارات الأسرية في تحقيق الاستقرار الأسري لدى المرأة، ولتحقيق هذا الهدف حاولت الباحثة التعرف على دور مكاتب الاستشارات الأسرية، ومستوى الاستقرار الأسرى، ثم التعرف على طبيعة العلاقة الارتباطية بين دور مكاتب الاستشارات الأسرية والاستقرار الأسري لدى عينة من السيدات في المجتمع المصري، ثم التنبؤ بالاستقرار الأسري من خلال دور مكاتب الاستشارات الأسرية، ولتحقيق هذا الهدف قامت الباحثة ببناء مقياسين أحداهما لقياس دور مكاتب الاستشارات الأسرية وبناء مقياس أخر لقياس الاستقرار الأسري (إعداد الباحثة/ ۲۰۲۱)، وتم التحقق من الخصائص السوسيومترية لهاتين الأداتين من خلال تطبيقهما على عينة استطلاعية قوامها (١٦٠) من السيدات في المجتمع المصري المترددين وغير المترددين على مكاتب الاستشارات الأسرية، ولاختبار صحة فروض البحث تم تطبيق الصورة النهائية للأداتين على عينة أخرى قوامها (١٦٠) من غير المشاركون بعينة التقنين، وأسفرت النتائج عن: أولا- ارتفاع مستوى دور مكاتب الاستشارات ثانيا- ارتفاع مستوى الاستقرار الأسري، ثالثا- وجود علاقة ارتباطية موجبة دالة إحصائيا بين دور مكاتب الاستشارات الأسرية وبين الاستقرار الأسري، رابعا- إمكانية التنبؤ بالاستقرار الأسرى من خلال دور مكاتب الاستشارات الأسرية. This research aims to identify the role of family counseling offices in achieving family stability for a sample of members of the Egyptian society, and to achieve this goal the researcher tried to identify the role of family counseling offices, and the level of family stability, then to identify the nature of the correlation between the role of family counseling offices and family stability among A sample of Egyptian society members, then predicting family stability through the role of family counseling offices. To achieve this goal, the researcher built two scales, one of them to measure the role of family counseling offices, and another scale to measure family stability (prepared by the researcher /2021), and the sociometric characteristics of these two were verified. The two tools, by applying them to an exploratory sample of (160) members of the Egyptian community who hesitated and did not hesitate to visit family counseling offices, and to test the validity of the research hypotheses, the final image of the two tools was applied to another sample consisting of (160) non-participants in the legalization sample, and the results resulted in: First - The high level of the role of consulting offices, secondly - the high level of family stability, third - the presence of a positive statistical function A between the role of family counseling offices and family stability, fourth- the possibility of predicting family stability through the role of family counseling offices.
Keywords: المؤسسات الاجتماعية -- الحياة الزوجية -- المشكلات الأسرية -- الإرشاد الأسري